Exploring online users´ attitudes and behaviors: the privacy paradox and its current motivations - Melleu, Anna Clara De Figueiredo (2021)
Individuals' privacy has become an essential theme to be addressed in today's growing digital world" Privacy Paradox" is the discrepancy between privacy concerns and actual behaviors This research aims to explore whether:- Users are still concerned about their online privacy- The elements of Privacy Cynicism has an impact on users' online behavior